Synthesis and preliminary gas permeation studies of a tubular NaA zeolite membrane (NZM). Issue 10 (3rd October 2017) - Xu, Nong; Lee, Sang Moon; Kim, Sung Su; Li, Anwu; Lim, C. Jim; Fotovat, Farzam; Schaadt, Achim; Grace, John R.
ABSTRACT: Different from traditional seeded method, NaA zeolite membranes (NZMs) were prepared by in situ synthesis onto the inner side of porous α -alumina tubular supports in a hydrothermal synthesis reactor. The influences of pretreatment of porous tubular support, temperature, time, and synthetic cycle for the synthesis of the zeolite membranes were investigated. The operating conditions were optimized. Characterization of the membranes by scanning electron microscopy and X-ray diffraction showed that the crystalline materials on the inner surface of the porous α -alumina tubes were NaA-type zeolite. Single- and binary-gas permeation tests were conducted. Single-component permeabilities of hydrogen and nitrogen through the NZM changed slightly when the transmembrane pressure difference varied from 80 to 420 kPa. Its selectivity for H2 relative to N2 was about 5.3, which was greater than that of the Knudsen diffusion. The separation factors of binary gases H2 /N2 and H2 /CO2 at 473 K were 3.9 and 5.7, respectively, again exceeding the Knudsen diffusion level. The separation of binary gases suggests that the NaA-type zeolite membranes on α -alumina substrate were defect free and able to provide molecular sieving. The results demonstrate that the unseeded synthetic method presented in this work is successful and reliable.